An Institutional Theory of Momentum and Reversal - Vayanos, Dimitri; Woolley, Paul (Review of Financial Studies, 2013)
[We propose a theory of momentum and reversal based on flows between investment funds. Flows are triggered by changes in fund managers' efficiency, which investors either observe directly or infer from past performance. Momentum arises if flows exhibit inertia, and because rational prices underreact to expected future flows. Reversal arises because flows push prices away from fundamental values. Besides momentum and reversal, flows generate comovement, lead-lag effects, and amplification, with these being larger for high idiosyncratic risk assets. A calibration of our model using evidence on mutual fund returns and flows generates sizeable Sharpe ratios for momentum and value strategies.]